IMPLEMENTATION OF THE LOVE CURRICULUM IN SHAPING CHARACTER BASED ON COMPASSION IN STUDENTS AND ITS IMPACT ON HARMONIOUS RELATIONSHIPS BETWEEN EDUCATORS AND STUDENTS: A LITERATURE REVIEW - Moh. Imron Rosidi; Aslan Aslan (Adisam Publisher, 2025)
This study aims to examine the implementation of the love curriculum as a learning approach that places the value of love as the main foundation in shaping student character and its impact on creating harmonious relationships between educators and students. Through a literature review method, this study analyses various scientific sources that discuss the concepts, strategies, and practices of the love curriculum in education, as well as how the value of love can strengthen social and emotional interactions in the learning environment. The results of the study show that the implementation of the love curriculum is effective in shaping love-based character, which includes empathy, honesty, and a sense of social responsibility in students. In addition, the consistent application of the value of love encourages harmonious relationships that increase learning motivation, effective communication, and reduce conflict between educators and students. This study emphasises that the love curriculum is not only idealistic but also a practical strategy that is relevant to improving the quality of education, requiring a strong commitment from all education stakeholders